(untitled) (Revista Apotheke, 2021)
The essay deals with Shila Joaquim’s creative process where she highlights Poetry as the main element of the structure of her way of creating and making art. From the place of a self-taught artist he relates not knowing to the freedom of creation, in this path he accesses memories and delineates paths taken in the production of some of the aforementioned works.